Design considerations for the engine repair section of a service facility - Nahornyi, M. (Запоріжжя: ТДАТУ, 2026)
The engine-repair department is intended for: • restoration of the engine’s base components (cylinder blocks, crankshafts, and camshafts); • assembly and testing of units (assembly of the crankshaft with the flywheel and clutch, and their balancing); • general engine assembly; • repair of auxiliary units (oil and water pumps, oil filters, etc.). The engine-repair department includes the following sections: the fitting-and-machining section and the assembly section. The basis for designing the department’s sections is the production program.
Keywords: diesel engine; production program